2021
DOI: 10.3390/ijgi11010021
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Temporal and Spatial Trends of Global Warming and Extreme Ocean Surface Temperatures: A Case Study of Canada

Abstract: In recent years, extreme weather has frequently occurred worldwide and caused significant disasters, including large-scale forest fires, rare heat waves, heavy rains, floods, and tornadoes. Those have caused unprecedented losses of human lives and property in some countries, affecting the livelihoods of many people. Climate change and natural disasters are the two hotspots of scientific research today, and there is a certain degree of correlation between the two. Although countries worldwide have long known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Canada is especially threatened by climate change, being reported to be experiencing warming at a rate double to that of the rest of the world on average (Wang et al, 2022) -attributable to its unique geographical setting (Ball, 2022). In the short term however, cooler areas of the province are expected to benefit positively from climate change -it has been observed that spring canola production across the last century has increased markedly nationwide, specifically correlating with increases to both temperature and precipitation due to climate change (Jannat et al, 2022) (Kutcher et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Canada is especially threatened by climate change, being reported to be experiencing warming at a rate double to that of the rest of the world on average (Wang et al, 2022) -attributable to its unique geographical setting (Ball, 2022). In the short term however, cooler areas of the province are expected to benefit positively from climate change -it has been observed that spring canola production across the last century has increased markedly nationwide, specifically correlating with increases to both temperature and precipitation due to climate change (Jannat et al, 2022) (Kutcher et al, 2010).…”
Section: Introductionmentioning
confidence: 99%